Empiric Antibacterial Therapy and Community-onset Bacterial Coinfection in Patients Hospitalized With Coronavirus Disease 2019 (COVID-19): A Multi-hospital Cohort Study. (21st August 2020) - Vaughn, Valerie M; Gandhi, Tejal N; Petty, Lindsay A; Patel, Payal K; Prescott, Hallie C; Malani, Anurag N; Ratz, David; McLaughlin, Elizabeth; Chopra, Vineet; Flanders, Scott A
Abstract: Background: Antibacterials may be initiated out of concern for bacterial coinfection in coronavirus disease 2019 (COVID-19). We determined prevalence and predictors of empiric antibacterial therapy and community-onset bacterial coinfections in hospitalized patients with COVID-19. Methods: A randomly sampled cohort of 1705 patients hospitalized with COVID-19 in 38 Michigan hospitals between 3/13/2020 and 6/18/2020. Data were collected on early (within 2 days of hospitalization) empiric antibacterial therapy and community-onset bacterial coinfections (positive microbiologic test ≤3 days). Poisson generalized estimating equation models were used to assess predictors. Results: Of 1705 patients with COVID-19, 56.6% were prescribed early empiric antibacterial therapy; 3.5% (59/1705) had a confirmed community-onset bacterial infection. Across hospitals, early empiric antibacterial use varied from 27% to 84%. Patients were more likely to receive early empiric antibacterial therapy if they were older (adjusted rate ratio [ARR]: 1.04 [1.00–1.08] per 10 years); had a lower body mass index (ARR: 0.99 [0.99–1.00] per kg/m 2 ), more severe illness (eg, severe sepsis; ARR: 1.16 [1.07–1.27]), a lobar infiltrate (ARR: 1.21 [1.04–1.42]); or were admitted to a for-profit hospital (ARR: 1.30 [1.15–1.47]). Over time, COVID-19 test turnaround time (returned ≤1 day in March [54.2%, 461/850] vs April [85.2%, 628/737], P < .001) and empiric antibacterial use (ARR: 0.71 [0.63–0.81] April vs March) decreased. Conclusions: The prevalence of confirmed community-onset bacterial coinfections was low. Despite this, half of patients received early empiric antibacterial therapy. Antibacterial use varied widely by hospital. Reducing COVID-19 test turnaround time and supporting stewardship could improve antibacterial use. Abstract : In 38 Michigan hospitals, early empiric antibacterials were prescribed to 56.6% (965/1705) of patients hospitalized with COVID-19, while 3.5% (59/1705) had a confirmed community-onset bacterial coinfection. Among hospitals, empiric antibacterial use varied from 27% to 84%.